2019
DOI: 10.1038/s41467-019-11144-6
|View full text |Cite
|
Sign up to set email alerts
|

Detecting topology freezing transition temperature of vitrimers by AIE luminogens

Abstract: Vitrimers are one kind of covalently crosslinked polymers that can be reprocessed. Topology freezing transition temperature (T v ) is vitrimer’s upper limit temperature for service and lower temperature for recycle. However, there has been no proper method to detect the intrinsic T v till now. Even worse, current testing methods may lead to a misunderstanding of vitrimers. Here we provide a sensitive and universal method by doping or swelling aggregation-induced-em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
135
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(136 citation statements)
references
References 38 publications
1
135
0
Order By: Relevance
“…S4 †) because the ionic interactions between TPPE and the PAMPS chain were relatively weak as they were largely dissociated in the solution, resulting in the increase in the motional freedom of TPPE than that in the TPPE-PAA hydrogel. In accordance with some recent studies, [27][28][29][30] this work showed that the uorescence enhancement of the AIE luminogen had a close relationship with the macromolecule motion ability and the supramolecular interaction; thus, AIE luminogens might be used as the indicator of the thermomotion of polymer chains in the solution state.…”
Section: Temperature-responsive Uorescencesupporting
confidence: 91%
See 1 more Smart Citation
“…S4 †) because the ionic interactions between TPPE and the PAMPS chain were relatively weak as they were largely dissociated in the solution, resulting in the increase in the motional freedom of TPPE than that in the TPPE-PAA hydrogel. In accordance with some recent studies, [27][28][29][30] this work showed that the uorescence enhancement of the AIE luminogen had a close relationship with the macromolecule motion ability and the supramolecular interaction; thus, AIE luminogens might be used as the indicator of the thermomotion of polymer chains in the solution state.…”
Section: Temperature-responsive Uorescencesupporting
confidence: 91%
“…[23][24][25][26][27][28] Besides, some groups reported the monitoring of the transition temperature by introducing AIE units into polymer chains, which illustrated the potential application of the AIE units as uorescent probes. For example, Bao et al developed a sensitive and reliable approach for the detection of the glass transition temperature (T g ) of polymers using tetraphenylethene derivatives as uorescent sensors; 29 Yang and coworkers proposed an efficient method to measure the topology freezing transition temperature (T v ) of a vitrimer by the uorescence change in the AIE molecules; 30 Wang et al reported enhanced uorescence emission around the lower critical solution temperature (LCST) by importing the AIE property into the thermo-responsive polymer. 31 These studies employed the characteristics of AIE for the indication of the polymer phase transition; however, there are few examples where AIE luminogens are utilized as uorescent indicators to characterize supramolecular interactions and macromolecular motions without aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper, Yang et al65 were able to employ a fluorescent probe to monitor network relaxation in vitrimers. Aggregation‐induced‐emission (AIR) luminogens are fluorescent organic compounds that are highly emissive when restriction of intramolecular motion (e.g., in an aggregated state) causes the dissipation of absorbed energy via radiation.…”
Section: Methods Of Characterizationmentioning
confidence: 99%
“…Our strategy for reprocessing traditional LCETs originated from our serendipitous finding . Recently we measured T v by an aggregation‐induced emission (AIE) probe technique.…”
Section: Introductionmentioning
confidence: 99%
“…We found that, as for vitrimers that contain a certain amount of transesterification catalyst, the traditional epoxy thermoset without any catalysts possesses the same topology freezing transition temperature (ca. 102 °C), which indicates a dramatic change of reaction rate . The existence of this transition, with or without the catalyst, indicates that the traditional epoxy thermosets should share a similar topology rearrangement potential and consequent reprocessability as typical vitrimers.…”
Section: Introductionmentioning
confidence: 99%